The impact of Euro-zone crisis on foreign direct investment inflows in the EU-15 - (:unkn) unknown (Inderscience Publishers, 2016)
The aim of this paper is to scrutinise the impact of financial crises on foreign direct investments (FDIs) of the EU-15 by using dynamic panel data analysis. The empirical analysis depicts that financial crisis is one of the most important determinants of FDI inflows in the EU-15. Our main finding is that contrary to global financial crisis, Euro-zone crisis has increased FDI inflows to Greece, Italy, Ireland, Portugal and Spain (GIIPS). Yet, FDI inflows in crisis time do not always indicate successful FDI policy. Copyright © 2016 Inderscience Enterprises Ltd.
Keywords: Dynamic panel data models; European Union; FDI; Financial crisis; Foreign direct investment